2015
DOI: 10.15446/revfacmed.v62n4.43754
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic performance of platelet-derived indices for the differential diagnosis of thrombocytopenia in pediatrics

Abstract: <p>Background. Platelet-derived indices have a well-established correlation with the differential diagnosis of thrombocytopenia in adult-based research. These indices include mean platelet volume, platelet distribution width, and platelet-large cell ratio.</p><p>Objective. To determine the values of platelet-derived indices in a pediatric population with diagnoses of thrombocytopenia and their etiologic correlation.</p><p>Materials and methods. Analytic observational diagnostictes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
1
9
0
2
Order By: Relevance
“…[ Table 5] Borkataky et al also noticed high mean PDW values except for non-megaloblastic subgroup of impaired production. [18] Similar results were obtained by Islam S et al [19] and Aponte-Barrios NH et al [20] Though the present study included all age groups, study by Aponte-Barrios NH et al in pediatric age group found that PDW can distinguish between thrombocytopenia due to an increase in the destruction of platelet and thrombocytopenia due to a reduction in platelet production. [20] …”
Section: Discussionsupporting
confidence: 89%
“…[ Table 5] Borkataky et al also noticed high mean PDW values except for non-megaloblastic subgroup of impaired production. [18] Similar results were obtained by Islam S et al [19] and Aponte-Barrios NH et al [20] Though the present study included all age groups, study by Aponte-Barrios NH et al in pediatric age group found that PDW can distinguish between thrombocytopenia due to an increase in the destruction of platelet and thrombocytopenia due to a reduction in platelet production. [20] …”
Section: Discussionsupporting
confidence: 89%
“…O diagnóstico é confirmado por exclusão de outras causas que levam a redução no número de plaquetas, como leucemia, linfomas, doenças infecciosas, HIV, neoplasias, hepatopatias, doenças genéticas e outras patologias autoimunes, devendo ser feita a avaliação da medula (biópsia e aspirado) para confirmar ou excluir a doença. Não há exames com especificidade e sensibilidade suficiente para confirmar a PTI BRASIL, 2013;CRUZ et al, 2011;AL-MULLA et al, 2009;APONTE-BARRIOS et al, 2014;SANTANA et al, 2013). No entanto, ARAKI (2018) demonstrou que a avaliação do tamanho das plaquetas por citometria de fluxo foi útil no diagnóstico de trombocitopenia e identificaram os parâmetros associados com manifestações de sangramento na mucosa ou órgão.…”
Section: Resultsunclassified
“… 14 However, study done by Aponte-Barrios in 2014 reported a high sensitivity and specificity for MPV, PDW and PLCR in diagnosis of immune thrombocytopenia and stresses on the use of these indices as screening tool. 9 Al-Sharifi proposed a cut off value of 9.9 fL for MPV with sensitivity and specificity of 100%. 15 Our study differ from above mentioned studies in that the platelet indices had poor sensitivity and specificity for diagnosing immune thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic importance of a screening test is measured by determining area under the reactive operative characteristic (ROC) curve. 9 A good test has a larger are under the curve (AUC) and vice versa A weak test has AUC of about .5 to .6 .A good test has the AUC of about .75 to .9. An excellent test has AUC of .97 to 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation